The Conflicts of Acts 1-8:3 in View of Recent Research on Religious Conflicts in Antiquity, Part Two: Enabling Conditions and Other Factors - Stenschke, Christoph W. (European journal of theology, 2017)
Part one of this essay (which appeared in the previous issue of this Journal) introduced recent theorising on religious conflict in antiquity. It examined the contested domains in the religious conflicts of Acts 1-8:3, namely the heritage of Israel, the identity, fate and significance of Jesus, the privilege and duty of instructing the people of Cod, authority in other spiritual matters, legitimate leadership of the people of Cod and public recognition/honour. Part two now examines the political, social, economic, cultural, psychological and transcendent enabling conditions on both sides of these conflicts which made their course and outcome possible. It also discusses traces of de-escalation and resolution, co-existence and co-operation and transition and assimilation. It closes with reflections on the significance of the conflict accounts of Acts 1-8:3 for the church today.